Role of the R349 Gene and Its Repeats in the MIMIVIRE Defense System - Mougari, Said; Abrahao, Jonatas; Oliveira, Graziele P.; Bou Khalil, Jacques Y.; La Scola, Bernard (Frontiers in Microbiology, 2019)
MIMIVIRE is a defense system described in lineage A Mimivirus (Mimiviridae family) that mediates resistance against Zamilon virophage. It is composed of putative helicase and nuclease associated with a gene of unknown function called R349, which contains four 15-bp repeats homologous to the virophage sequence. In a previous study, the silencing of such genes restored susceptibility to the virophage. Moreover, the CRISPR cas-4 like activity of the nuclease has recently been characterized. In this study, a recently isolated Mimivirus of lineage A with R349 gene lacking 3 of 4 repeats was demonstrated to be susceptible to Zamilon. To reinforce the importance of the R349 gene in MIMIVIRE system, we developed and presented, for the 1st time to our knowledge, a protocol for Mimivirus genomic editing. By knocking out R349 gene in a Mimivirus lineage A, we observed the replication of Zamilon, indicating that this gene is critical for the resistance against this specific group of virophages.